2022
DOI: 10.3389/fgene.2022.1042772
|View full text |Cite
|
Sign up to set email alerts
|

The barley DIR gene family: An expanded gene family that is involved in stress responses

Abstract: Gene family expansion plays a central role in adaptive divergence and, ultimately, speciation is influenced by phenotypic diversity in different environments. Barley (Hordeum vulgare) is the fourth most important cereal crop in the world and is used for brewing purposes, animal feed, and human food. Systematic characterization of expanded gene families is instrumental in the research of the evolutionary history of barley and understanding of the molecular function of their gene products. A total of 31,750 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…DIR gene family members are widely distributed in various plant species. Advances in genome sequencing technology have facilitated the identification of DIR genes in several plant genomes, including Arabidopsis [ 3 ], Capsicum annuum [ 15 ], Solanum lycopersicum [ 1 ], Solanum melongena [ 16 ], Oryza sativa [ 11 , 17 ], Hordeum vulgare [ 18 ] and Glycine max [ 14 ]. In this study, a total of 57 NtDIRs in tobacco and 33 StDIRs in potato were identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DIR gene family members are widely distributed in various plant species. Advances in genome sequencing technology have facilitated the identification of DIR genes in several plant genomes, including Arabidopsis [ 3 ], Capsicum annuum [ 15 ], Solanum lycopersicum [ 1 ], Solanum melongena [ 16 ], Oryza sativa [ 11 , 17 ], Hordeum vulgare [ 18 ] and Glycine max [ 14 ]. In this study, a total of 57 NtDIRs in tobacco and 33 StDIRs in potato were identified.…”
Section: Discussionmentioning
confidence: 99%
“…A study on tomato ( Solanum lycopersicum ) identified 31 DIR genes [ 1 ], while 24 DIR genes were found in eggplant ( Solanum melongena L.) [ 16 ]. Additionally, a total of 54 rice DIR genes were found in rice ( Oryza sativa ) [ 11 , 17 ], 64 DIR genes in barley ( Hordeum vulgare ) [ 18 ], and 54 DIR genes in soybean ( Glycine max ) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results clearly show that DIR13 plays an important role in salt and drought stress tolerance for different assays including seed germination, root growth and progressive stress to soil-grown plants. This is in agreement with previous findings based on expression analyses, suggesting the role of dirigent genes in various stress responses (Paniagua et al ., 2017; Luo et al ., 2022). For instance, recent studies have shown that silencing of pepper CaDIR7 weakened plant defense and increased susceptibility to biotic and salt stresses (Khan et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Dirigent proteins have been shown to act in initiating lignan synthesis [ 44 ]. Both dirigent and lignan are proposed to have vital roles in defense responses [ 67 , 68 , 69 ]. Particularly, some dirigent proteins boost disease resistance by directly promoting lignan accumulation [ 70 ].…”
Section: Multifarious Functions Of Lignin In Plant Defense Responsesmentioning
confidence: 99%